(untitled) (Al-Aasar, 2025)
The Economic Development of any country is based on the correct and healthy Relationship between two elements, Employers and Employees, that is, there should be a fair balance in their rights and duties. Vehicle of Economy If these two wheels work properly in their respective places at the required speed, the set economic goals can be achieved But history is a witness that the wage and labor class has always been oppressed and after the cruel revolution of the employer, the workers organized and established their own associations and conflicts arose between employers and wage earners. The workers go on strike and the boss locks out. As a result the vehicle of the economy slows down or stops. Inflation and poverty will increase and the country will suffer from economic instability. The owner is ready to give the right of service and wages to the laborer and the laborer does not work according to the set rules. To solve it, man made laws according to his intellect, but these conflicts did not decrease significantly, the reason being that he turned away from the laws revealed by Allah. Therefore, its appropriate solution is given in the Seerah of the Prophet (peace be upon him).